21st century geopolitics: integration and development in the age of 'continental states'. Issue 4 (2nd October 2017) - Rivarola Puntigliano, Andrés
ABSTRACT: 21st century geopolitics: integration and development in the age of 'continental states'. Territory, Politics, Governance . There is a need, in the 21st century, to analyse the interconnection between development and regional integration with a renewed attention to geopolitics. The aim of this paper is to explore the links between states, the economy and the international system in an ongoing process of transformation generating a new world order. Drawing on geopolitical theory, this study advances the argument that in the 21st century, those states in search of increasing autonomy apply strategies of regional integration and development-oriented policies, following a path to constructing new grossraums centred on states that are continental in scope. For this analysis the study proposes using a geopolitical perspective – here called 'classical geopolitics' – emphasizing the territorial dimension of state making, which includes economic policies and the formation of national identities. Particular attention is given to the spatial motif observed in international systems of promoting paths towards states of continental scope.